Comparison of Market Efficiency and Microeconomic Volatility Transmission between Islamic and Conventional Stock Markets: Empirical Evidence from the JII and the IHSG - Rizki, Oktavera; Ridwan, Muhammad; Soemitra, Andri; Yusrizal (Outline Publisher, 2026)
Purpose: This study aims to analyze market efficiency and the transmission of micro-volatility between the Jakarta Composite Index (IHSG) and the Jakarta Islamic Index (JII) using high-frequency data from September 22 to October 20, 2025. The primary objective is to evaluate the volatility of returns, co-movement, microstructure volatility clustering, and the buffering effect of Sharia-compliant indices. Methods: The study uses logarithmic continuous returns to assess return volatility and co-movement. Descriptive statistics are employed to examine market fluctuations, while the volatility clustering effect and rapid shock transmission between the two indices are analyzed. Pre-test and post-test evaluations, along with observational analysis, are used to examine the relationship and behavior of these indices during the study period. Results: The findings reveal that both IHSG and JII exhibit significant short-term fluctuations, indicative of typical micro-volatility in emerging markets. However, JII shows relatively lower volatility and fewer extreme negative returns, suggesting that Sharia screening provides a stabilizing effect on the market. The study also identifies a strong co-movement between the two indices, highlighting high short-term integration despite brief divergences due to differences in index structure and liquidity profiles. Additionally, the analysis confirms volatility clustering, with calm periods followed by sharp movements, and rapid shock transmission between the indices.